2008
DOI: 10.1080/14767050802353572
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous hemoperitoneum in a twin pregnancy complicated by endometriosis

Abstract: A primigravida with a twin pregnancy presented acute abdominal pain and hypovolemic shock at 33 weeks of gestation. Ultrasound examination revealed the absence of fetal heartbeat in one fetus and serious bradycardia in the other without echographic signs of placental abruption. Immediate laparotomy revealed massive hemoperitoneum resulting from spontaneous rupture of right uterine vessels. Two demised fetuses were delivered by cesarean section and hemostasis was accomplished. According to the literature report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 8 publications
0
10
0
1
Order By: Relevance
“…In most cases there was considerable blood loss requiring extensive transfusion of blood and blood products. The surgical challenge posed by this presentation is considerable, as demonstrated by detailed literature accounts (20,23).…”
Section: Perinatal and Maternal Outcomesmentioning
confidence: 97%
“…In most cases there was considerable blood loss requiring extensive transfusion of blood and blood products. The surgical challenge posed by this presentation is considerable, as demonstrated by detailed literature accounts (20,23).…”
Section: Perinatal and Maternal Outcomesmentioning
confidence: 97%
“…The causes and management of spontaneous hemoperitoneum post second trimester were reviewed (Table 1) [2345678910111213]. …”
Section: Discussionmentioning
confidence: 99%
“…In other cases, active bleeding is described from endometriosic lesions with or without tears [4,13,14]. Inoue et al suggested that endometriosis may be involved in the rupture of these vessels [5].…”
Section: Discussionmentioning
confidence: 99%
“…It is defined as an unprovoked intraperitoneal bleeding that may be idiopathic or related to many causes such as uterine rupture, placental abruption, spontaneous ruptures of uterine varicosities, placenta percreta, liver or splenic rupture in preeclampsia, trauma, ectopic pregnancy and other rare causes such as a spontaneous rupture of a splenic artery aneurysm, or a ruptured appendix. The most common cause of SH is spontaneous utero-ovarian vessel rupture in pregnancy [1][2][3][4][5][6][7][8][9][10][11][12]. SH in pregnancy occurred before labour for 61%, intrapartum for 18% and puerperal for 21%.…”
Section: Discussionmentioning
confidence: 99%